Formyl peptide receptor 1 signalling promotes experimental colitis in mice. (March 2019) - Di Paola, Rosanna; Fusco, Roberta; Gugliandolo, Enrico; D'Amico, Ramona; Cordaro, Marika; Impellizzeri, Daniela; Perretti, Mauro; Cuzzocrea, Salvatore
Graphical abstract: Abstract: Inflammatory bowel disease is characterised by intricate immune cell interactions with tissue cells and such cross-talks can become deregulated. The formyl peptide receptor 1 (Fpr1) is expressed by both immune and stromal cells including epithelial cells. We evaluated the development of the physiopathology of the DNBS induced colitis in Fpr1 KO mice on the C57BL/6 genetic background compared to C57BL/6 genetic background animals. We have assessed both macroscopic and histological markers of the diseased, together with the immunohistochemical and molecular changes. DNBS-treated Fpr1 KO mice showed a i) reduction in weight loss, ii) lower extent of colon injury and iii) an increase in MPO activity. Molecular analyses indicated that in absence of Fpr1 there was reduced NF-κB translocation into the nucleus, cytokines levels, FOXP3 and GATA3, CD4, CD8 and CD45 expression as well as a dysregulation of TGF-β signalling. In addition, the colon of DNBS-injected Fpr1 KO mice displayed a lower degree of expression of Bax and higher expression of Bcl-2 compared correspondent WT mice. Finally, intravital microscopy investigation of the microcirculation post-DNBS instillation revealed a lower degree of neutrophil-endothelial cell rolling and adhesion - mediated by P-selectin and ICAM-1 – in Fpr1 KO mice. All the main outcome in the study have a P-value, statistical significance of evidence, less than 0.05. We provide evidence for an important pathogenic role of mouse Fpr1 in experimental colitis, an outcome effected through modulation of immune cell recruitment together with a modulation of local cellular activation and survival.